De Althusser a Badiou. El sujeto, el objeto y la política. Un debate entre el estructuralismo y el posestructuralismo (2013)
This article is part of an ongoing debate about Marxism, which forms as a result of a historical phenomenon: the collapse of real socialism, coupled with the vagaries of contemporary capitalism, it is assumed that the “crisis of Marxism” is a product of a much broader debate into the political philosophical thought. On this second point is that we will try, mark certain questions relating to the subject-object analyzing the thought of two authors from the Marxist tradition. The pair Badiou-Althusser demarcates a kind of synthesis that encompasses the particular problem is more general: the relationship / tension inward Marxist discourse between structuralism and the linguistic turn, or more precisely poststructuralism.